Exploring the Mismatch Between Teacher Demand-Supply in Sub-Sahara Africa: Ghana as Case Study - Ntim, Stephen (Mediterranean Journal of Social Sciences, 2013)
This study presents an analysis of the factors affecting the supply and demand of school teachers in Ghana. The findingssuggest that the major pull causing the mismatch in teacher supply-demand equation can be summed up under: a) economicdemand, b) demographic factors and c) market forces. Sixty percent of those sampled constituting 162 of the respondentswere of the view that there was a significant correlation between remuneration and supply while the other 40% (108) notattributing it to remuneration per se, nevertheless saw a link between supply and other economic issues such as end of servicebenefit. Ninety five percent of respondents were of the view that teacher upgrading in higher market premium courses ininstitutions of higher learning exacerbate teacher attrition into other better paid jobs: an indication of non-incentives pullingteachers from the teaching profession. The objective of the study is to contribute to advocacy on teacher issues, especiallyincreased resources as well as innovative funding for the employment of sufficient number of teachers.